Memristor interpretations based on constitutive relations. (October 2017) - Wu, Wei; Deng, Ning
Abstract: The attractive memristor is interpreted based on its constitutive relation. The memory property of the memristor is explained, along with the explanation on its three fingerprints: (1) Pinched hysteresis loop; (2) Hysteresis lobe area decreases as frequency increases; (3) Pinched hysteresis loop shrinks to a single-valued function at infinite frequency. Where the magnetic flux is in Strukov's memristor is also introduced. Resistive elements including the memristor are taken as an example to argue that the constitutive relation determines the electrical property of a circuit element and diagram method is used to distinguish different elements in the resistive element series.